A Comparison of Recurrent Non-specific Low Back Pain Patients and Healthy Subjects in Variability of Anticipatory Postural Adjustments - Rozita Hedayati; Seddigheh Kahrizi; Mohammad Parnian-Pour; Fariba Bahrami; Anoushirvan Kazem-Nezhad; Bahram Mobini; Sara Taherian (University of Social Welfare and Rehabilitation Sciences, 2010)
Objective: The purpose of this study was to ivestigate of the postural strategies variability in low back pain patients, as a criterion in the adaptability evaluation of this system to the environmental demands and comparison of patients with healthy persons and also the importance of psychological factors associated with pain as an effective factor in postural disturbances was assessed. Materials & Methods: This analytical, cross-sectional and case-control study was performed on twenty one recurrent non-specific low back pain patients whom had been selected simply and conveniently and twenty one healthy persons whom had been matched with patients. The electromyographic activity of Deltoid, External Oblique, Transverse Abdominis / Internal Oblique and Erector Spinae muscles of each person was recorded in 75 rapid arm flexion with maximum acceleration. To study the patient's avoidance belief and disability, two standard tools Fear-Avoidance Belief Questionnaire (FABQ) and Roland-Morris Questionnaire were used respectively. Data were analyzed by MANOVA and Pearson correlation coefficient. Results: The results showed that chronic low back pain patients exhibit less variability in their anticipatory postural adjustments than the control group(P=0.047). However, the decrease in variability of the timing of anticipatory postural adjustments of External Oblique(P=0.45) and Erector Spinae(P=0.6) muscles was not significant. The correlation between the timing variability of anticipatory postural adjustments and fear-avoidance belief questionnaire scores was significant(P=0.006), however there was no significant correlation between this variable and disability(P=0.09) in the patients. Conclusion: There is a decrease in variability of postural control system of recurrent non-specific low back pain patients that can result in the persistence of pain and chronicity by decreasing the adaptability to environmental demands. The restoration of variability to postural control system should be taken into consideration in rehabilitation of these patients.